Hubungan Usia, Hemoglobin, dan Indeks Massa Tubuh dengan Perubahan Ukuran Tumor pada Kemoterapi Neoadjuvant Kanker Serviks Stadium IB2 dan IIA2 di RSUP Dr. M. Djamil Padang - Nisa Ayu Farma; Syamel Muhammad; Asterina Asterina (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. On stage IB2 and IIA2 of cervical cancer standard treatment such as neoadjuvant chemotherapy is required. The changes in tumor size of this therapy is influenced by several factors, among others are Age, Hb, and BMI.Objective. To determine the relationship of Age, Hb, and BMI with changes in tumor size to neoadjuvant chemotherapy of servical cancerMethods. This of research was analytical research with using a cohort retrospective design with a total sample of 35 patients. The research instrument used was a medical record then analyzed with a with a dependent sample t-test and simple regression linier correlation test.Results. The result obtained a moderate negative power relationship between age and changes in tumor size (R= -0,412 ; P= 0,014), and there was no significant relationship between changes in tumor size with hemoglobin rate ( R= -0,107 ; P= 0,541), and BMI ( R= -0,117 ; P= 0,545).Conclusion. There is a significant relationship between age and changes in tumor size, and there is no significant relationship between hemoglobin and body mass index with changes in tumor size.